Elevation - King, Stephen, 1947-; Geyer, Mark (New York : Scribner, 2018)
c
"A novel"--Dust jacket.
Keywords: Castle Rock (Me. : Imaginary place) -- Fiction; Community life -- Fiction; Lesbians -- Fiction; Weight loss -- Fiction; Maine -- Fiction; Thrillers (Fiction).